2013
DOI: 10.1021/jo401243b
|View full text |Cite
|
Sign up to set email alerts
|

Anthrone and Related Hydroxyarenes: Tautomerization and Hydrogen Bonding

Abstract: The keto-enolization of hydroxyl-substituted naphthols and 9-anthrols has been investigated by means of CBS-QB3 calculations. An excellent agreement between experiment and theory is found for the energetics for the anthrone (5) ⇌ anthrol (6) equilibrium, with an enthalpy of tautomerization, Δ(t)H, of 3.8 kcal mol(-1). In contrast, 1-naphthol is the preferred tautomer with a Δ(t)H = -9.0 kcal mol(-1). Substitution of the hydrogens at the adjacent carbons by hydroxyl groups leads to the formation of strong intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 72 publications
0
28
2
Order By: Relevance
“…17,31,32 In a computational study reported in 2013, the keto-enol tautomerization equilibria of various naphthols and 9-anthrols and the effect of hydrogen bonding on these equilibria were investigated by Korth and Mulder. 33 Finally, it should be noted that the first and second acid dissociation constants (pK a1 and pK a2 ) for 1,8-naphthalenediol (7) in water were determined to be 6.71 and >13.00, respectively, 34 whereas 1-naphthol (8) has a pKa value of 9.22 in water. 35 While the X-ray structure of 1,8-naphthalenediol (7) has not been reported, the crystal structure of compound 9 was shown to display an intramolecular hydrogen bond between the two -OH groups of the 1,8naphthalenediol core (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…17,31,32 In a computational study reported in 2013, the keto-enol tautomerization equilibria of various naphthols and 9-anthrols and the effect of hydrogen bonding on these equilibria were investigated by Korth and Mulder. 33 Finally, it should be noted that the first and second acid dissociation constants (pK a1 and pK a2 ) for 1,8-naphthalenediol (7) in water were determined to be 6.71 and >13.00, respectively, 34 whereas 1-naphthol (8) has a pKa value of 9.22 in water. 35 While the X-ray structure of 1,8-naphthalenediol (7) has not been reported, the crystal structure of compound 9 was shown to display an intramolecular hydrogen bond between the two -OH groups of the 1,8naphthalenediol core (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…4 It has been found that the calculated equilibrium ratio between anthrone and 9-anthrol in a non-hydrogen-bonding solvent is in excellent agreement with experiment. 4 Next to benzannulation, the tautomeric ratio in solution can be influenced significantly through the formation of intra-and intermolecular hydrogen bonds.…”
Section: ■ Introductionmentioning
confidence: 54%
“…4 Next to benzannulation, the tautomeric ratio in solution can be influenced significantly through the formation of intra-and intermolecular hydrogen bonds. 4 Despite the fact that the thermodynamics of the keto−enolization for the hydroxyarenes may now be well understood, the precise mechanism and, therefore, the rates are difficult to predict. In general, the presence of an acid appears to be a prerequisite for a facile transformation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[16] In such ac ase, no anthracene radicalc ation was observed during the reaction. In competition with the reverse electron transfer from [(Bn-TPEN)Mn III (O)] + to the anthracene radical cation, fast OC À transfer from [Mn III (O)] + to the anthracene radical cation may occur to produce 9-hydroxyanthracene (the enol form;S cheme 2, reaction pathway b), [23] which is known to be tautomerized to anthrone (the keto form;S cheme 2, reaction pathway c), [24] and [Mn II ] 2 + .A nthrone, in equilibrium with 9-hydroxyanthracene,i s furthero xidized by an electron transfer from 9-hydroxyanthracene to [Mn IV (O)] 2 + ,f ollowed by fast OC À transfer and an intramolecular hydrogen-atom transfer to produce anthrahydroquinone and [Mn II ] 2 + (Scheme 2, reaction pathway d). Anthrahydroquinone is furthero xidized by an electron transfer from anthrahydroquinone to [Mn IV (O)] 2 + ,f ollowedb yp roton and hydrogen-atom transfers to produce anthraquinone, [Mn II ] 2 + ,a nd H 2 O( Scheme 2, reaction pathway e).…”
Section: Resultsmentioning
confidence: 99%